PENGARUH UKURAN PERUSAHAAN, INTENSITAS MODAL, PERTUMBUHAN PENJUALAN DAN INTENSITAS PERSEDIAAN TERHADAP PENGHINDARAN PAJAK - Setiawan, Irwan; Bayu Putra, Fajar Tri (Publika Citra Media, 2024)
This study aims to examine the Effect of Company Size, Capital Intensity, Sales Growth, and Inventory Intensity on Tax Avoidance. The population in this study were all companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019 - 2023. The sampling technique used purposive sampling and obtained 31 samples. The analysis method used was multiple linear regression using e-views software version 10. The results of this study indicate that Company size has a significant effect on tax avoidance, capital intensity has no effect on tax, sales growth has no effect on tax avoidance, inventory intensity has a significant effect on tax avoidance, and company size, capital intensity, sales growth, Inventory intensity simultaneously have a significant effect on tax avoidance.